High intensity interval training or sprint interval training: What is the gold standard for energy system development in team-based field sports? - Bishop, C. R. (Journal of Australian Strength and Conditioning, 2021)
The ability of Team Based Field Sport athletes to perform repeated short duration sprints throughout a match is integral to individual and team performance. This implies that athletes require well developed aerobic and anaerobic abilities to be successful for their respective sports. Utilising online databases from 2010-present, 17 articles were reviewed assessing the impact of High Intensity and Sprint Interval Training on aerobic and anaerobic adaptations that can be applied to Team Based Field Sport Athletes. The results indicate that both modalities are effective for energy system development, with Sprint Interval Training proving marginally more effective for Anaerobic Adaptations, whilst there is no significant difference in the aerobic adaptations. To determine the more applicable modality, coaches should consider factors outside of physiological adaptation, including but not limited to phase of training, session duration, energy expenditure and recoverability.